2016
DOI: 10.1136/archdischild-2015-309600
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal outcomes of waterbirth: a systematic review and meta-analysis

Abstract: This systematic review and meta-analysis did not identify definitive evidence that waterbirth causes harm to neonates compared with land birth. However, there is currently insufficient evidence to conclude that there are no additional risks or benefits for neonates when comparing waterbirth and conventional delivery on land.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 42 publications
(21 reference statements)
1
37
0
4
Order By: Relevance
“…According to literature, waterbirth is safe for women with healthy pregnancies and low‐risk births (Davies et al, 2015; Nutter et al, 2014; Taylor et al, 2016; Ulfsdottir, Saltvedt, & Georgsson, 2018; Vanderlaan et al, 2018) and should thus be presented as an alternative for pregnant women who consider ways to give birth. Our findings illustrate that while women appreciate the opportunity to give birth in water, a positive birthing experience can be hampered if the equipment is unsuitable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to literature, waterbirth is safe for women with healthy pregnancies and low‐risk births (Davies et al, 2015; Nutter et al, 2014; Taylor et al, 2016; Ulfsdottir, Saltvedt, & Georgsson, 2018; Vanderlaan et al, 2018) and should thus be presented as an alternative for pregnant women who consider ways to give birth. Our findings illustrate that while women appreciate the opportunity to give birth in water, a positive birthing experience can be hampered if the equipment is unsuitable.…”
Section: Discussionmentioning
confidence: 99%
“…Research has not identified any increase in maternal mortality or morbidity for women who give birth in water with healthy full‐term pregnancies and low‐risk births in cephalic presentation (Nutter, Meyer, Shaw‐Battista, & Marowitz, 2014; Ulfsdottir, Saltvedt, & Georgsson, 2018). No differences has been observed in low risk births between children born in and out of water with regard to neonatal outcomes, including Apgar scores, postnatal infections, umbilical cord samples, and admissions to neonatal intensive care (Davies, Davis, Pearce, & Wong, 2015; Taylor et al, 2016; Vanderlaan, Hall, & Lewitt, 2018), indicating that waterbirth is a safe alternative for many women.…”
Section: Introductionmentioning
confidence: 99%
“…In case reports, researchers demonstrated that when secondary apnea is present (due to fetal hypoxia), neonates may exhibit a gasping reflex at the time of waterbirth that can result in the inhalation of water and potentially make resuscitation and ventilation more challenging. 13,16,22 If an indeterminate fetal heart rate pattern is detected, further evaluation is indicated. F. Mortality.…”
Section: Risksmentioning
confidence: 99%
“…No maternal deaths have been reported, and only isolated fetal deaths have been attributed to immersion during labor or birth. 12,13,[16][17][18] VI. STANDARD REQUIREMENTS TO FACILITATE HYDROTHERAPY During the prenatal period, health care providers should discuss the potential use of water during labor and/or birth with all low-risk women as part of an overall discussion and education regarding evidencebased options for pain relief.…”
Section: Risksmentioning
confidence: 99%
See 1 more Smart Citation